2018
DOI: 10.5216/rbn.v1i1.43247
|View full text |Cite
|
Sign up to set email alerts
|

Características morfológicas e químicas de lâminas foliares de Paspalum spp.

Abstract: O objetivo deste trabalho foi avaliar o potencial de utilização de lâminas foliares da gramí­nea tropical Paspalum spp. para o consumo animal por meio das características morfofisiológicas, da anatomia quantitativa e das características químicas. O experimento foi realizado no período de agosto de 2009 a junho de 2010, no município de Dourados -MS. Foram avaliadas oito espécies de Paspalum spp., sendo as sementes cedidas pela Embrapa Pecuária Sudeste. O delineamento experimental utiliza­do foi o de blocos ao a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
1
4
2
3
Order By: Relevance
“…The greatest CP value was recorded on the apical segment (segment 5) of phytomer 16 (Table 5 ), and did not differ from those segments with smaller percentages of central rib mass and greater values of SLA. These findings are in line with those of Lucena et al 23 , which indicated positive correlations between CP and SLA (r = 0.52; P = 0.0010) on leaf blades of Paspalum spp.. The difference in CP detected on segment 5 of phytomer 10 may have been consequence of leaf maturity stage, similarly to all segments of phytomers 8 and 9, since cell wall components and fibre increase and digestibility and crude protein decrease as leaf age increases 7 , 14 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The greatest CP value was recorded on the apical segment (segment 5) of phytomer 16 (Table 5 ), and did not differ from those segments with smaller percentages of central rib mass and greater values of SLA. These findings are in line with those of Lucena et al 23 , which indicated positive correlations between CP and SLA (r = 0.52; P = 0.0010) on leaf blades of Paspalum spp.. The difference in CP detected on segment 5 of phytomer 10 may have been consequence of leaf maturity stage, similarly to all segments of phytomers 8 and 9, since cell wall components and fibre increase and digestibility and crude protein decrease as leaf age increases 7 , 14 .…”
Section: Discussionsupporting
confidence: 94%
“…In this context, given the relationship between herbage nutritive value and the anatomic composition of plant tissues 20 , the study regarding leaf anatomy and morphology may provide an useful tool for discriminating promising genotypes in qualitative terms in the early phases of evaluation of new forage materials 22 . It may also help with the identification of factors limiting intake 23 and the results used to develop plant three-dimensional growth models that could be used to predict nutritive value and nutrient intake by grazing animals as well as to define targets for grazing management strategies.…”
mentioning
confidence: 99%
“…Com relação à %PB, o maior valor foi registrado no segmento apical (segmento 5) do fitômero 16 (Tabela 8), não diferindo dos segmentos que apresentaram menores proporções de nervura central e maiores valores de área foliar específica (AFE). Esses resultados estão de acordo com de (Lucena et al, 2017), que identificou correlações positivas entre %PB e AFE (r = 0,52; P = 0,0010) em lâminas foliares de Paspalum spp. A diferença observada no segmento 5 do fitômero 10, pode ter sido em razão do amadurecimento da folha, assim como em todos os segmentos dos fitômeros 8 e 9, visto que o avanço na idade da folha resulta em incremento nos componentes de parede celular, aumento dos teores de fibra e queda nos coeficientes de digestibilidade e nos teores de proteína bruta (Paciullo, 2002;Rezvani Moghaddam e Wilman, 1998 (Church, 1988).…”
Section: Características Anatômicasunclassified
“…Assim, por relacionar-se com o valor nutritivo da forragem (Paciullo et al, 2001), o estudo anatômico do tecido de lâminas foliares, associado às suas características morfológicas, pode ser ferramenta útil na discriminação de genótipos promissores em termos qualitativos nas fases iniciais de avaliação de novos materiais forrageiros (Gomes et al, 2011). Pode também auxiliar na identificação dos fatores que limitam seu consumo (Lucena et al, 2017) e os resultados utilizados para desenvolver modelos de crescimento tridimensional de plantas como ferramenta para predizer o valor nutritivo e a ingestão de nutrientes de animais em pastejo.…”
Section: Introductionunclassified
See 1 more Smart Citation